Effects of the subanesthetic dose of esketamine on postoperative sleep quality in patients undergoing modified radical mastectomy: a randomized, double-blind controlled trial - Chen, Ying; He, Junchen; Huang, Rong; Pan, Zhuoqi; Zhong, Min; Zhang, Wenxuan (Frontiers in Medicine, 2025)
BackgroundBreast cancer is the most common malignant tumor among women worldwide. Surgical intervention is a critical component of treatment, yet the associated stress and anxiety can significantly disrupt postoperative sleep quality. Emerging evidences suggest that esketamine may offer benefits in alleviating emotional distress and enhancing sleep. The purpose of this study was to observe the effects of intraoperative subanesthetic dose of esketamine on the sleep of patients undergoing modified radical mastectomy.MethodsThis randomized, double-blind, controlled trial enrolled 145 female patients, who were randomly assigned to either the esketamine group (Group E, n = 72) or the control group (Group C, n = 73). Patients in Group E received esketamine (0.2 mg/kg loading dose, followed by 0.1 mg/kg/h infusion), while those in Group C received saline (0.2 mL/kg loading dose, followed by 0.1 mL/kg/h infusion). The primary outcome was the total score on the Richards-Campbell Sleep Questionnaire (RCSQ) measured on postoperative day (POD) 1. Secondary outcomes included recovery time, the incidence of postoperative adverse events and rescue analgesia, Visual Analogue Scale (VAS) pain scores, short-form McGill’s Pain Questionnaire (SF-MPQ) sensory and affective scores, and Pittsburgh Sleep Quality Index (PSQI) scores.ResultsNo significant differences were observed in the total RCSQ scores on POD 1 between Group E and Group C (median [interquartile range]: 46 [32–68] vs. 54 [40–71], p > 0.05). Recovery time was significantly longer in Group E compared to Group C (8 [5–11] vs. 6 [4–11] minutes; p = 0.02). There were no significant differences in the incidence of adverse events or remedial analgesia within 48 h postoperatively. Furthermore, no significant differences were observed between the groups in pain VAS scores, and SF-MPQ sensory or affective scores at 4, 24, and 48 h postoperatively. PSQI scores on POD 30 were not significantly different between the groups (p > 0.05).ConclusionFor female patients without pre-existing sleep disorders undergoing modified radical mastectomy, intraoperative subanesthetic esketamine may not significantly impact postoperative sleep quality but potentially contribute to a prolonged recovery time.Trial registrationThis trial was registered at the Chinese Clinical Trial Registry on July 03, 2022 (https://www.chictr.org.cn; Registration number: ChiCTR2200061818).